Locating and imaging composite damage based on frequency spectrum detection of lamb waves - Zhang, Wenchao; Su, Chenhui; Zhang, Yuhang; Yang, Hongjuan (Frontiers in Physics, 2022)
Lamb wave is widely concerned in damage detection of composite structures due to its long propagation distance and strong sensitivity to damage. In order to solve the problem of damage information extraction, high-precision imaging positioning of damage is realized. A damage location imaging method based on lamb signal spectrum is proposed. The damage location imaging of composite materials is realized by simulation and experiment respectively. Firstly, the feasibility of the algorithm is verified by simulation. The circular sensor array is arranged in the structure. Each sensor acts as an actuator and rotates clockwise to generate Lamb waves, while other sensors collect signals. The frequency spectrum of the signal is extracted to calculate the damage factor, and the probability imaging algorithm is used to realize the single damage and multiple damage location imaging. Then, the damage imaging localization is realized through experiments. Finally, the resistant noise characteristic of the proposed algorithm is analyzed. The results show that both single damage and multiple damage can be located in strong noise environment. It shows that this method can realize damage imaging directly without preprocessing the original signal. It has great potential in damage location imaging under strong noise environment.